Ageing in Irish Writing Strangers to Themselves - Ingman, Heather (Springer International Publishing, 2018)
Age is a missing category in Irish literary criticism and this book is the first to explore a range of familiar and not so familiar Irish texts through a gerontological lens. Drawing on the latest writing in humanistic, critical and cultural gerontology, this study examines the portrayal of ageing in fiction by Elizabeth Bowen, Molly Keane, Deirdre Madden, Anne Enright, Iris Murdoch, John Banville, John McGahern, Norah Hoult and Edna O'Brien, among others. The chapters follow a logical thematic progression from efforts to hold back time, to resisting the decline narrative of ageing, solitary ageing versus ageing in the community, and dementia and the world of the bedbound and dying. One chapter analyses the changing portrayal of older people in the Irish short story. Recent demographic shifts in Ireland have focused attention on an increasing ageing population, making this study a timely intervention in the field of literary gerontology.